Prognosis of Syntocinon Infusion on Scar Uterus Cotonou-Benin...... - TONATO EPSE BAGNAN, JOSIANE ANGÉLINA ADJOUA; OBOSSOU, A. A.A.; HOUNKPATIN, BENJAMIN IGNACE B.; LOKOSSOU, MSHS; PERRIN, RENÉ-XAVIER (My University, 2016)
Objective: This study aims to assess prognosis of actively managed childbirths through oxytocin infusion into uterus with prior caesarean section in the Lagoon University Teaching Hospital for Mother and Child (CHU-MEL). Method: It was a case control study of descriptive and analytical type based on 82 observations of actively managed delivery with oxytocin infusion into uterus with caesarean section scar at the Maternity over a two-year period from February 1, 2014 to December 31, 2015. Results: Actively managed childbirth with oxytocin accounted for 8.4% of childbirths through uterus with Csection scar; success rate was 79.3%. Caesarean section was necessary for delivery in 19.5% of the cases. The mean age of our parturient women was 29.5 years. The mean pregnancy bearing rate of parturient women was 3.5 pregnancies with extremes of 2 and 7 pregnancies. Most parturient women had an inter delivery interval between 2 and 5 years i.e. a 78%. The surgical outcomes of first caesarean section were not characterized by any particularity. In this research work, we did not note any case of maternal death, but we registered 1 case of uterine rupture (1.2%). We also registered 3 neonatal deaths, i.e. a 3.6% rate including 1 death after vaginal birth i.e. 1.2%. These deaths were due to uterine rupture (1 case) and neonatal distress (2 cases). Conclusion: Despite all the constraints of obstetrical practice in Sub-Saharan Africa, using Oxytocin may be contemplated for the management of labor on uterus with c-section scar.
Keywords: Oxytocin infusion; Uterus; Caesarean section